Sistem Pendukung Keputusan Pemilihan Supplier Obat Menggunakan Metode Simple Additive Weighting - Erlyta Hares; Shofa Shofia Hilabi; Agustia Hananto (Ma'soem University, 2023)
Determining drug suppliers for pharmacies choosing suppliers based on the price of the goods offered, the quality of the goods while in transit, whether the goods are received according to the order or not, and whether or not the delivery time for the goods reaches the pharmacy quickly. The main problem in supplier selection is decision making in choosing a good and efficient supplier and supported by problems that usually occur when the number of drugs sent does not match what was ordered, the packaging is damaged, the date is close to the expiration date. A decision support system for selecting drug suppliers with the help of the Simple Additive Weighting (SAW) method can assist pharmacies in making the right decisions on drug supplier selection to be chosen by pharmacies. The step in solving existing problems is to choose the best supplier by using the Simple Additive Weighting (SAW) method as a support for this research, in the Simple Additive Weighting (SAW) method which has ten (10) alternative suppliers that will be used to determine the best supplier, of course only one becomes the best supplier selection decision. Of the 10 suppliers selected after determining the value, the best results were obtained at Pt. Pharmaceutical Chemistry.